The changing role of salespeople - Donaldson, Bill (Henry Stewart Talks, 2010)
Examples of change drivers in a sales context, A shift from transaction to relationship selling and its implications, Changing sales processes by suppliers, Changing salespersons' behavior, Changing customers' perceptions, Activities of winning sales organizations, Requirements for superior sales performance, New organizational designs for successful selling